The impact of the Covid-19 pandemic on the stage of endometrial cancer at diagnosis - Audrey P. Garrett; Benjamin C. Seidman (Elsevier, 2023)
Background: Endometrial cancer generally presents at an early stage affording a high rate of surgical cure. Early in the Covid-19 pandemic it was suggested that treatment of tumors with favorable pathologic features might safely be delayed. Objective: We hypothesized that disruption to health care services during the pandemic would impact the stage at presentation for these patients. Here we compare the stage at presentation of Endometrial Cancer in the months immediately preceding the pandemic to the stage at presentation during the pandemic. Study design: Charts of patients presenting with Endometrial Cancer between January 1, 2018 and April 30, 2022 were reviewed. March 1, 2020 separated the "pre-pandemic" era from the "pandemic" era. Data was collected regarding patient age, body mass index (BMI), tumor stage, histology, grade, size, and depth of invasion. Results: 322 of 374 (86.09%) of surgically staged patients presented with FIGO stage I disease "pre-pandemic" compared to 263 of 329 (71.73%) of surgically staged patients in the "pandemic" cohort (p =.029). 2.08% pre-pandemic compared to 5.48% during the pandemic presented with FIGO stage IV (p =.015). Conclusion: We found a significant difference in the stage at presentation in endometrial cancer patients, a statistic which may be attributed to the disruption of healthcare services caused by the Covid-19 pandemic.